2010
DOI: 10.1007/s11605-009-1089-y
|View full text |Cite
|
Sign up to set email alerts
|

Eleven Cases of Postoperative Hepatic Infarction Following Pancreato-Biliary Surgery

Abstract: Attention should be paid to inadvertent injury of hepatic artery to prevent hepatic infarction. Hepatic infarctions after pancreato-biliary surgery seldom extend to the entire liver and most of them are able to be treated without intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Early in 1989, Brown et al [ 40 ] reported a case of a patient who underwent LGA embolization and suffered complications of hepatic ischaemic necrosis owing to a replaced left hepatic artery arising from it. Miura et al [ 41 ] also documented 11 patients in 2010 who had postoperative hepatic infarction after undergoing pancreato-biliary surgery and analyzed the underlying causes. In 2 of the 11 patients, the cause of hepatic infarction was inadvertent ligation of the RHA during surgery, and one patient 1 a variant RRHA originating from the SMA.…”
Section: Discussionmentioning
confidence: 99%
“…Early in 1989, Brown et al [ 40 ] reported a case of a patient who underwent LGA embolization and suffered complications of hepatic ischaemic necrosis owing to a replaced left hepatic artery arising from it. Miura et al [ 41 ] also documented 11 patients in 2010 who had postoperative hepatic infarction after undergoing pancreato-biliary surgery and analyzed the underlying causes. In 2 of the 11 patients, the cause of hepatic infarction was inadvertent ligation of the RHA during surgery, and one patient 1 a variant RRHA originating from the SMA.…”
Section: Discussionmentioning
confidence: 99%
“…[11] Additionally, failure to preserve the arterial blood supply to the liver is particularly serious in patients undergoing PD because biliary ischemia may lead to biliary leakage or an anastomotic ischemic stricture. [12] As we have described in the current cases, there are 2 possible strategies for managing aberrant HAs; namely, preserving the trunk of the aberrant artery or removing it and performing arterial reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…When these infarctions do occur, they are usually caused by surgical, traumatic, or septic etiologies. [1][2][3] They have also been described in the medical literature as being secondary to vasculitis -specifically polyarteritis nodosa -via hepatic vessel inflammation and occlusion. [1,4] Haratake et al described a case of hepatic infarction diagnosed during the autopsy of a 44-year-old man suffering from polyarteritis nodosa.…”
Section: Discussionmentioning
confidence: 99%